EFFECTIVE TRAFFIC CONGESTION MANAGEMENT USING AUTOMATIC TOLL COLLECTION ON URBAN HIGHWAYS (CASE STUDY: SADR MULTILEVEL HIGHWAY) - Mahmoud Safarzade; Amir Rasuli (پژوهش‌های زیرساخت‌های عمرانی, 2014)
Population and traffic demand growth have caused over-capacity traffic volume, unpleasant level of service, and traffic congestion in urban freeway/highway networks. Various demand management strategies are used these days which have significant role in network performance boosting. Pricing is one of these popular strategies which is effectively used world-wide. In this paper, a reasonable toll price is determined for Sadr multilevel highway and pricing effects on this highway is studied.